PRICING PROBLEM IN PUBLIC PASSENGER TRANSPORT SERVICES AND MANNERS OF REMUNERATION OPERATORS (Perner's Contacts, 2011)
The problem which deals with pricing in public passenger transport is discussed in this article. This problem is a reset of Regulation (EC) No 1370/2007 and its application to practise. Because of unpreparedness authority, Slovak agreements of 2011 don’t accept the principle of neutrality and the reasonable profit is specified as a percentage of costs. The article states manners of remuneration operators in Europe.
Keywords: a reasonable profit; public passenger transport; the risk (deals with operating public passenger transport